The effect of disease duration on the incidence of peripheral arterial disease in young adults with systemic lupus erythematosus - Merlyn, M; Setyohadi, Bambang; Soebardi, S; Harimurti, K (Indonesian Rheumatology Association, 2013)
Background: Peripheral arterial disease is a chronic complication that affects morbidity and mortality in SLE patient. However, there were only a few of researches studying the relationship of disease duration andÂ peripheral arterial disease event overseas and it hasnever been studied in Indonesia.Objectives: To obtain information about the increased event of peripheral arterial disease in women of 40 years old or younger with SLEâs duration of five years or longer compared with less than five years.Methods: This was a case control study conducted between June - August 2012 at Cipto Mangunkusumo hospital, Jakarta. Subjects were women of 40 years old or younger with SLE who visited Rheumatolgy and Allergy-Immunlogy outpatient clinic. They were assignedto case and control groups and traced retrospectively using interview and medical record. The relationship between disease duration and peripheral arterial disease was estimated using OR and the role of confounding factors was analysed using logistic regression one byone, resulted in fully adjusted OR.Results: A total of 90 subjects were recruited, 18 subjects in case group and 72 subjects in control group.Traditional risk factors were similiar in both groups. In multivariat analysis, there was a relationship between disease duration 5 years or longer and peripheral arterialdisease with fully adjusted OR 1,9 (95%CI 0,575-6,543). Older age and steroid therapy were the confounding factors.Conclusion: There was an increased event of peripheral arterial disease in women of 40 years old or younger with SLEâs duration five years or longer compared withsubjects having the disease duration less than five years, but this increase was not statistically significant.Keywords: Peripheral arterial disease, lupus erythematosus systemic, disease duration